A new species of the bee genus Ammobates Latreille, 1809 from sub-Saharan Africa (Hymenoptera: Apidae) - (:unkn) unknown (My University, 2021)
The cleptoparasitic bee Ammobates (Ammobates) roggeveldi n. sp. is described from a female specimen collected in western South Africa. This is only the second species of the genus recorded from sub-Saharan Africa.
Keywords: African Research